KEWAJIBAN BAKO MENAFKAHI ANAK SETELAH AYAH WAFAT: STUDI TENTANG NAFKAH DI KECAMATAN SUNGAI TARAB - Dheana Permata Sandy; Khairina Khairina (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
This research examines how the obligation of bako to support children whose father has died in Minangkabau, how is the view of Islamic law towards the obligation of bako to provide for children whose father has died in Sungai Tarab District. The purpose of this research is to find out the obligation of Bako to provide for children whose father has died in Minangkabau and to find out how Islamic law views the obligation of Bako to provide for children whose father has died in Sungai Tarab District. This type of research is field research. Data collection was carried out through interviews with respondents, namely niniak mamak, religious scholars, cadiak clever and bundo kanduang in Sungai Tarab District, the form of interviews used was semi-structured interviews. Data processing is done by analyzing the data using descriptive qualitative analysis techniques. The data analysis technique that the writer uses is Data Reduction, Data Presentation, and Conclusion Drawing. The responsibility of the father's family to provide for the child after the father dies in Sungai Tarab Subdistrict, as stated in article 104 of the Compilation of Laws which reads "If the father has passed away, the cost of breastfeeding shall be borne by the person who is responsible to the father or his guardian." A living must be given to children who have not been able to work to meet their own needs, especially for children who are still babies or are still breastfeeding, even though the father's family has provided for the child but does not meet their needs because they do not routinely provide a living, especially for the father's family which does not provide for the child at all even though the child has tried asking for a living, it can be seen that the responsibility or obligation of the father's family to provide for the child after the father dies is not by Islamic law.